Network monitor with packet siffer - Mujahid, Jamaluddin (2010)
Network Monitor with Packet Sniffer is software for operating network monitor application. It has been designed for use in any computer in a simple approach. This software interacts easily with user as only buttons are the way of interaction. Network Monitor with Packet Sniffer is a real-time way to manage the network-communication via monitoring, capturing and sniffing in order to fulfill the project purpose. The result will be packet monitoring traffic, and packet information that can be analyzed in the future. So, it is very convenient to user especially for networking students. This thesis consists of 6 chapters. Chapter 1 will discUss about the Introduction to the System. These first chapters briefly explain about the objective of the system, problem statement and project scopes. Chapter 2 and 3 are about the Literature Review and Methodology of the project. Chapter 2 and 3 will discuss about the methods that will be used, elaborating the sources from the research, and deciding the best tools that will be used to build the system. Chapter 4, Implementation; are about the documentation of the processes during the development of the system, including any modification that been plan and made. While the last, Chapter 5 Result and Discussion and Chapter 6 Conclusion. Chapter 5 will explain about the result that has collected from the analysis and tests of the system along with the constraints and suggestion to enhance the system performance. Conclusion and overall summary of the system, data, methodology, implementation, and the suggestions are in the matter of the discussion on of the chapter 6.